Variasi Spasial Kepadatan Cacing Kacang di Pantai Toronipa Sulawesi Tenggara - Bahtiar Bahtiar; Muhammad Fajar Purnama; Ria Trisnawati; Ela Anjarsari; Wa Ode Defina Mahmud (Jurnal Ilmu Pertanian Indonesia, 2024)
The density of peanut worms is concentrated in the subtidal zone and is closely related to the substrate where they live. This research aims to determine spatial variations in peanut worm density. This research was carried out at Toronipa Beach, Southeast Sulawesi from June 2020 to February 2021. Peanut worms were collected using a hand scoop to a depth of ±10 cm in a 10x10 m2 quadrat transect at each station. Data were analyzed using standard formulas and tested using Mann-Whitney and linear regression. The results showed that the highest density of peanut worms was found at station II with a mean value of 12±104 ind/10m2 which was significantly different from stations I and III with densities of 9±52 ind/10m2 and 7±124 ind/10m2 respectively. Five types of seagrass were identified, namely Cymodocea rotundata, Enhalus acoroides, Halodule uninervis, Halophila minor, and Thalassia hemprichii. The number of seagrass species found at stations I, II, and III were 1, 2, and 5, respectively. Peanut worm density was positively correlated with seagrass density with a coefficient of determination of 86.45%. Water quality tends to be the same at all stations, except that organic matter is higher than at stations I and II. The dominant fine sand fraction was found at stations I and III, while very coarse sand was dominantly found at station II. The density of peanut worms on Toronipa Beach is determined by a combination of seagrass density, high levels of organic matter, and the dominant texture of the coarse sand substrate. Keywords: peanut worm, spatial density, Sulawesi, water quality